Industrial policy and development the political economy of capabilities accumulation - Dosi, Giovanni, 1953-; Cimoli, Mario; Stiglitz, Joseph E. (Oxford : Oxford University Press, 2009)
This volume addresses the issue of state intervention in industry & markets. It provides a comprehensive critique of the policies informed by the Washington Consensus. Building on this critique, the editors bring together essays by leading experts in the field which focus on instances of successful industrial policies & interventions.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Economic policy; Economic development